Summer observations, 1978, Northwest Iowa - Nigus, Tomet al (1978)
Field report titled "Summer observations, 1978, Northwest Iowa," submitted by Tom Nigus. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of summer, 1978. Epson - sheet feed/flatbed